Solve for a 2(a-4)+8=3a-8

Math
2(a-4)+8=3a-8
Simplify 2(a-4)+8.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
2a+2⋅-4+8=3a-8
Multiply 2 by -4.
2a-8+8=3a-8
2a-8+8=3a-8
Combine the opposite terms in 2a-8+8.
Tap for more steps…
Add -8 and 8.
2a+0=3a-8
Add 2a and 0.
2a=3a-8
2a=3a-8
2a=3a-8
Move all terms containing a to the left side of the equation.
Tap for more steps…
Subtract 3a from both sides of the equation.
2a-3a=-8
Subtract 3a from 2a.
-a=-8
-a=-8
Multiply each term in -a=-8 by -1
Tap for more steps…
Multiply each term in -a=-8 by -1.
(-a)⋅-1=(-8)⋅-1
Multiply (-a)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1a=(-8)⋅-1
Multiply a by 1.
a=(-8)⋅-1
a=(-8)⋅-1
Multiply -8 by -1.
a=8
a=8
Solve for a 2(a-4)+8=3a-8

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top